Emerging diagnostic and therapeutic opportunities in food allergy - Balsiger, Lukas Michaja; Würgler, Oliver M.; Sampson, Hugh A.; Eggel, Alexander (Frontiers in Immunology, 2026)
Food allergy is characterized by acute onset of symptoms affecting multiple organ systems following the ingestion of otherwise innocuous food antigens. The prevalence of this potentially life-threatening disease is globally increasing and poses a significant burden on society and healthcare systems. In this review, we summarize the pathophysiology of food allergy focusing on pre-clinical evidence of how oral tolerance is broken and the role of systemic and mucosal immunoglobulin E (IgE) in food allergy. Diagnosing food allergy is complex and requires a multimodal approach. Importantly, the diagnostic accuracy of currently available tests is variable, and in vivo testing runs the risk of inducing anaphylaxis in patients. We summarize established diagnostic modalities and provide an overview of novel approaches that are currently in development to improve diagnostic accuracy while minimizing discomfort and risk of anaphylaxis. Finally, we comment on available treatment modalities and provide an outlook of new therapeutic options in clinical trials or under development.